IMPLEMENTASI PROGRAM KELUARGA HARAPAN (PKH) DALAM UPAYA PENINGKATAN KELUARGA SEJAHTERA DI KAMPUNG SUMBER REJEKI DISTRIK KURIK KABUPATEN MERAUKE - Eka Sugiarti Setianingrum; David Laiyan; Syahrabudin Husein Enala; Frederikus Antonius Mana (Papsel Journal of Humanities and Policy, 2025)
This study aims to analyze the implementation of the Family Hope Program (PKH) in Sumber Rejeki Village by assessing aspects such as policy objectives and targets, resources, organizational characteristics, implementer attitudes, inter-organizational communication, as well as the economic, social, and political environment. The research method used is a qualitative approach with in-depth interviews conducted with key informants, including policy implementers, PKH assistants, and beneficiaries. The findings indicate that the PKH policy's objectives are well understood by the target community, but there are challenges related to uneven aid distribution, leading to social injustice among more vulnerable groups. The available resources, while adequate, have not been optimally utilized to reach all impoverished communities, especially those in remote areas. The characteristics of the implementing organization show good coordination, but improvements are needed in transparency and communication with the public, particularly those not registered as beneficiaries. The professional and empathetic attitude of the implementers greatly supports the program's success, although there are shortcomings in communication and outreach to the general public. The economic, social, and political environment plays a significant role in the successful implementation of PKH, with challenges such as social jealousy and local political factors affecting aid distribution. Therefore, it is recommended to enhance transparency in the data collection and aid distribution processes, strengthen the capacity of social assistants, and expand outreach efforts to ensure that the PKH program is more equitable and effective in achieving its goals.